Online Learning in the Face of COVID-19 Pandemic: Assessment of Students’ Satisfaction at Chitwan Medical College of Nepal - Sharma, K.; Deo, G.; Timalsina, S.; Joshi, A.; Shrestha, N.; Neupane, H.C. (Kathmandu University Medical Journal, 2020)
Background Online learning can play a vital role in the process of teaching and learning during Corona Virus Disease 2019 (COVID-19) pandemic. However, learners’ satisfaction is extremely important in effective implementation of the online learning, especially at institutions where it is newly adopted. Objective To assess satisfaction towards online learning and its predictors among students at Chitwan Medical College, Bharatpur. Method A web-based cross-sectional survey was undertaken among 434 undergraduate and postgraduate students from various academic programs who had participated in the online classes started during this COVID-19 pandemic. A structured questionnaire consisting of 31 items (5-point Likert scale) covering four major student satisfaction domains (learners’ dimensions, technological characteristics, instructors’ characteristics and course management and coordination) was distributed to the students using Google Form. Result More than half (53.5%) of the students were satisfied with the online learning, while 29.7% gave neutral views. Bivariate analyses found that all four domains scores were positively correlated with each other as well as with the students’ overall satisfaction towards learning. In multivariate analysis, female gender [aOR: 2.72, p = 0.013], WiFi as internet modality for learning [aOR: 3.36, p = 0.001) and learners’ dimension score [aOR: 1.27, p<0.001] were the significant predictors of students’ satisfaction. Conclusion Although recently adopted, the satisfaction of the students towards online classes appears good, and prioritizing the identified predictors and working on the weak links could assist in enhancing students’ satisfaction and better outcomes.